Pengaruh Brand Image, Korean Wave, Sikap Fanatisme, dan Brand Ambassador terhadap Keputusan Pembelian Ultra Milk Edisi Kolaborasi Stray Kids - Valentia Eka Ardani; Krisna Mutiara Wati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
Ultra Milk is a milk brand using UHT (Ultra High Temperature) technology and one of the products that dominate the Indonesian market. The rising trend of South Korean culture has led Ultra Milk to collaborate with South Korean entertainment artists. Capitalizing on fanaticism, Ultra Milk chose Stray Kids as a brand ambassador by issuing a limited edition photocard. The study aims to determine the effect of brand image, Korean wave, fanaticism, and brand ambassador on purchasing decisions for Ultra Milk products in the Stray Kids collaboration edition. Using a quantitative approach. Research data sources come from primary and secondary data. Primary data was obtained by distributing questionnaires to respondents. Secondary data sources are obtained from journals and books. Data collection techniques using non-probability sampling (purposive sampling). The research sample was 168 respondents with the criteria of Stray Kids fans, aged 20-25 years, and had purchased Stray Kids Ultra Milk products. The data was processed using SmartPLS 4.0 software. The results showed that brand image, Korean wave, fanaticism attitude, and brand ambassador have a positive and significant effect on purchasing decisions.